The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000519952
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Nonscarring Alopecia in Women: Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> There is no clear-cut evidence in the existing medical literature of an association between iron deficiency and nonscarring alopecia. <b><i>Objective:</i></b> The objective of the study was to conduct a systematic review of the medical literature on the prevalence of iron deficiency in women with nonscarring alopecia and compare their ferritin levels with those of women without this condition. <b><i>Methods:</i></b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
10
0
3
Order By: Relevance
“…This may be attributed to the fact that in our population, patients tend to seek medical attention at a later stage, after trying various home remedies without success. A large meta-analysis done which included studies from countries all over the world also demonstrated a strong relationship between iron deficiency and non-scarring hair loss in women 17 . In our study we did not find any noteworthy difference in the serum ferritin levels between the males and females.…”
Section: Discussionmentioning
confidence: 97%
“…This may be attributed to the fact that in our population, patients tend to seek medical attention at a later stage, after trying various home remedies without success. A large meta-analysis done which included studies from countries all over the world also demonstrated a strong relationship between iron deficiency and non-scarring hair loss in women 17 . In our study we did not find any noteworthy difference in the serum ferritin levels between the males and females.…”
Section: Discussionmentioning
confidence: 97%
“…Lower serum levels of vitamin D and ferritin have been observed in patients with non-cicatricial alopecias compared to the healthy population. 50 , 51 Nevertheless, there is yet no evidence of FPHL improvement with the supplementation of these substances. There is also no evidence of the benefit of biotin and zinc supplementation in healthy patients with FPHL.…”
Section: Clinical Treatmentsmentioning
confidence: 99%
“…40 Low serum ferritin (<40 μg/L) with concurrent symptoms of iron deficiency, including fatigue, pallor, dyspnea on exertion, or hair loss, should prompt treatment with supplemental iron. [41][42][43] Generally, ferrous (Fe2 + ) salts are preferred to ferric (Fe3 + ) salts, as the former is more readily absorbed through the duodenal mucosa 44 and is the more common formulation in commercially available supplements in the United States. 45 Oral supplementation with ferrous sulfate 325 mg (65 mg elemental iron) tablets is the first-line therapy for iron deficiency anemia.…”
Section: Clinical Utility Of Serum Ferritinmentioning
confidence: 99%